COUNSELING SYSTEM INTEGRATED ON THE WEB UNIT COUNSELING SERVICES FOR THE DEPARTMENT OF INFORMATIC ENGINEERING AND COMPUTER FACULTY OF ENGINEERING, STATE UNIVERSITY MAKASSAR - Sanatang Sanatang; Jumadi M Parenreng; Irvanshah Irvanshah (Jurnal Media Elektrik, 2024)
The aim of this research is to produce an integrated counseling information system on the web of the counseling service unit of the department of informatics and computer engineering, Faculty of Engineering, Makassar State University and find out the results of system testing using ISO 25010 with 8 testing aspects. This research is a type of software design research (software development) and uses a prototype design model with stages: gathering requirements, building a prototype, evaluating the prototype, coding the system, testing the system, evaluating the system, and using the system. The subjects of this research were students from the Department of Informatics and Computer Engineering, Makassar State University. Data collection instruments were carried out through validation test sheets, student response questionnaires, and system expert assessment instruments. The results obtained from this research are: (1) Functional suitability of the system created is 100% "Acceptable" criteria. (2) Performance efficiency obtained a result of 83.0% in the grade B "Good" category. (3) Usability obtained a percentage of 89% 98 respondents with the criteria "Very Good". (4) Compatibility shows that the system is made compatible with browsers so that it is expressed properly without causing problems. (5) Security obtained a grade of A+ "Very Good" in terms of security and no dangerous viruses were found on the system. (6) Reliability obtained as a percentage of 100% so it can be concluded that it meets the reliability aspect. (7) Maintainability obtained from the instrumentation, consistency and simplicity aspects can be categorized as good and meets the standards. Portability shows that the system can be accessed in a variety of different browsers. Based on the test results, it was concluded that the counseling information system integrated on the web of the counseling service unit of the informatics and computer engineering department, Faculty of Engineering, Makassar State University was suitable and acceptable for use.